SERVICE EXCELLENCE OF SALES ASSISTANT TO CUSTOMERS IN ORDER TO INCREASE SALES IN PT. ASTRA INTERNATIONAL TOYOTA AUTO 2000 BRANCH SUKUN - MALANG - Jawwadurrohman, Abdul Jabbar (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
Service Excellence is one term that evolved into today's marketing management science. Excellent service can actualize customer loyalty, so it is expected that the company's sales continue to increase. In order to build customer loyalty, Toyota dealers rely on personnel at the front liner, one of them is a Sales Assistant (SAS), which has an obligation to provide excellent services to customers. There are 6 (six) variable-rate service (service excellence) to customers who simultaneously carried out by the SAS as well. The variables of service excellence, among others: (1) the ability, (2) attitude, (3) appearance, (4) attention, (5) the action, and (6) accountability. Service excellence variables are understood, believed and done by the SAS in order to increase sales in AUTO 2000 Sukun-Malang branch. Service excellence variable is also a full concern and as a matter of evaluation for the Branch Manager or Supervisor, thus becoming one of the important materials in trainings conducted by the company. That from the six (6) variables excellence SAS service provided to the customer has a different order of priority for the SAS of AUTO 2000 Sukun-Malang branch. However, the results of this study, the majority of SAS convey that attitude is the main variable that they have prioritized for display to the customer, and this is recognized by the Supervisor and Head of Branch in AUTO 2000 Sukun-Malang branch.Â Keywords: Service excellence, Sales Assistant (SAS), Astra International, Toyota Â AUTO 2000.